English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-07-03 10:51:10 · 4 answers · asked by Lregofins34 2 in Science & Mathematics Mathematics

4 answers

By the sine difference identity,

sin(a - b) = sin(a)cos(b) - sin(b)cos(a)

Therefore,

sin(3x)cos(2x) - cos(3x)sin(2x) =
sin(3x - 2x) =
sin(x)

2007-07-03 11:30:45 · answer #1 · answered by Puggy 7 · 0 0

That's sin(3x-2x) = sin x,
since
sin(a-b) = sin a cos b - cos a sin b.

2007-07-03 11:23:25 · answer #2 · answered by steiner1745 7 · 1 0

sin 3x cos 2x − cos3xsin 2x =sin(3x-2x)=sin x

2007-07-03 10:56:23 · answer #3 · answered by zohair 2 · 1 1

sin 3x cos 2x − cos3xsin 2x
= sin(3x - 2x)
= sin(x).

2007-07-03 10:55:32 · answer #4 · answered by Anonymous · 1 1

fedest.com, questions and answers